Design of a CMOS voltage reference using current-model approach - De Souza, Flávio Q. [UNESP]; Oki, Nobuo [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
A voltage reference with low sensibility to temperature and power-supply that can generate flexible reference values (from milivolts to several volts) is proposed. Designed for AMS 0.35μm CMOS process, the circuit provides a stable output voltage working in the temperature range of -40-150°C. The proposed reference provides a nominal output voltage of 1.358V with a power-supply of 3.3V. © 2011 IEEE.
Keywords: Bandgap voltage reference; complementar to absolute temperature (CTAT); proportional to absolute temperature (PTAT); voltage reference; CMOS processs; CMOS voltage reference; Output voltages; Power supply; Reference values; Temperature range; CMOS integrated circuits; Voltage measurement